An assessment of information literacy competency among international students in University of Malaya / Isma’ila Isa Zuru - Isma’ila Isa , Zuru (2017)
This study focused on information literacy competency among international postgraduate students in University of Malaya. The aim of the study was to understand if there are differences in information literacy competency among international postgraduate students. Several studies have been conducted with regards to information literacy competency among international students in several countries and institutions. Few have been conducted in the University of Malaya with regards to information literacy competency among international postgraduate students. This is the justification for this research was to look at information literacy competency among international postgraduate students in the University of Malaya. A survey method was used during the study with a self-report questionnaire containing 40 items on a likert scale of 1-5. An inferential statistics was conducted to analyze the dependent and independent variables. The latest version of SPSS was used for the analysis of data collected. An independent sample t test was conducted and in some instances a one way anova was used to analyze the findings. The result of the study indicated that there is a significant mean difference in terms of information literacy competency among international students. The differences are between the variables age, gender, program of study, country official language and mode of study. This study justified the findings on previous studies on the differences in information literacy competency among international students in different countries and institutions.